METTL3-IGF2BP3-axis mediates the proliferation and migration of pancreatic cancer by regulating spermine synthase m6A modification - Guo, Zhenyun; Zhang, Xiang; Lin, Chengjie; Huang, Yue; Zhong, Yun; Guo, Hailing; Zheng, Zhou; Weng, Shangeng (Frontiers in Oncology, 2022)
Spermine synthase (SMS) is an enzyme participating in polyamine synthesis; however, its function and role in pancreatic cancer remains elusive. Here we report that SMS is upregulated in pancreatic cancer and predicts a worse overall survival and significantly promotes the proliferation and migration of pancreatic cancer cells. Excessive SMS reduces the accumulation of spermidine by converting spermidine into spermine, which activates the phosphorylation of serine/threonine kinase (AKT) and epithelial-mesenchymal transition (EMT) signaling pathway, thereby inhibiting pancreatic cancer cell proliferation and invasion. Moreover, SMS was identified as the direct target of both methyltransferase like 3 (METTL3) and insulin like growth factor 2 mRNA binding protein 3 (IGF2BP3), which directly bind to the m6A modification sites of SMS and inhibit mRNA degradation. Knockdown of METTL3 or IGF2BP3 significantly reduced the SMS protein expression and inhibited the migration of pancreatic cancer. We propose a novel regulatory mechanism in which the METTL3-IGF2BP3 axis mediates the mRNA degradation of SMS in an m6A-dependent manner to regulate spermine/spermidine conversion, which regulates AKT phosphorylation and EMT activation, thereby inducing tumor progression and migration in pancreatic cancer.